Advancing eco-friendly tourism through integrated zero-waste management strategies - Rizkia Syafriadi; Sakir (Indonesian Journal of Applied Environmental Studies, 2025)
This study examines the implementation of zero-waste management as a strategic approach to promoting eco-friendly tourism in Wirokerten Tourism Village, Yogyakarta. The rapid growth of tourism activities often results in increased volumes of waste that are inadequately managed, thereby posing serious threats to environmental sustainability and reducing the overall quality and attractiveness of tourism destinations. The primary aim of this study is to explore the application of plastic waste management concepts within community-based tourism practices in Wirokerten Tourism Village. Through the adoption of a zero-waste approach, the village seeks to integrate the core principles of reduction, reuse, and recycling into its tourism planning, management, and daily operational practices. This research employs a qualitative case study methodology, incorporating field observations, in-depth interviews with key local stakeholders, and document analysis to examine how zero-waste initiatives are incorporated into tourism development processes in Wirokerten. The findings reveal that active community participation, consistent support from local government institutions, and collaborative environmental governance mechanisms are critical factors contributing to the effectiveness and sustainability of the zero-waste programs. Specific initiatives, including waste segregation at the household and tourism facility levels, composting of organic waste, and eco-education activities targeting visitors, significantly enhance the village’s image as an environmentally responsible and sustainability-oriented tourism destination. Nevertheless, several challenges persist, particularly in relation to limited funding availability, capacity building constraints, and the need to foster long-term behavioral change among both residents and tourists (Rachmawati et al., 2024). This study contributes to the broader discourse on sustainable tourism by illustrating how zero-waste practices can be systematically integrated into tourism governance at the village level. The findings provide practical insights for policymakers, local communities, and tourism managers seeking to advance eco-friendly and sustainable tourism models in Indonesia and comparable contexts worldwide.